ASSESSING THE INFLUENCE OF ENTREPRENEURIAL SELF-EMPLOYMENT ON HUMAN DEVELOPMENT INDEX IN NIGERIA (Journal of the Management Sciences, 2024)
development index in Nigeria. The specific objective was to examine the influence of entrepreneurial self-employment to Nigerian human capital development. An ex-post facto research design was adopted in the study. Secondary data were collected from the National Bureau of Statistics for a period of 16 years, spanning the period from 2007 to 2022. Data were analysed using descriptive tools and inferential analysis. The hypothesis was validated using estimates from robust least square regression at a 5% significance level. The finding revealed that entrepreneurial self-employment significantly enhances the Nigerian human development index. In conclusion, entrepreneurial self-employment has a transformative potential to drive socioeconomic progress and improve human well-being. The study therefore recommended that by recognising and supporting the role of entrepreneurship in development strategies, Nigeria can unlock new pathways for sustainable and inclusive growth, ultimately leading to a more prosperous and equitable society.
Keywords: Entrepreneurial Self-Employment, Human Development Index, Entrepreneurial Development, Nigeria